Porttinari - a Large Multi-genre Treebank for Brazilian Portuguese - Pardo, Thiago Alexandre Salgueiro; Duran, Magali Sanches; Lopes, Lucelene; Felippo, Ariani Di; Roman, Norton Trevisan; Nunes, Maria das Graças Volpe (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2021: Anais do XIII Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2021)
This paper presents the project of a large multi-genre treebank for Brazilian Portuguese, called Porttinari. We address relevant research questions in its construction and annotation, reporting the work already done. The treebank is affiliated with the “Universal Dependencies” international model, widely adopted in the area, and must be the basis for the development of state of the art tagging and parsing systems for Portuguese, as well as for conducting linguistic studies on morphosyntax and syntax for this language.